Urban Digital Twin and urban planning for sustainable cities - Alessandra Barresi (Techne)
Cities nowadays need to have long-term visions and perspectives to achieve the ambitious targets for which vast investments are being made. They need to act with competence and capability-based planning, and to come up with suitable solutions. Technology is unquestionably a factor of crucial importance when aiming for these targets. Digital innovation, based on data knowledge, analysis and projection, is crucial to tackle the most demanding challenges of our times. The methodological approach proposed here is an Urban Digital Twin applied to cities as a predictive model to obtain a projection of their development in terms of sustainability.